2020
DOI: 10.1016/j.bbr.2019.112336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enriched housing on the neuronal morphology of mice that lack zinc transporter 3 (ZnT3) and vesicular zinc

Abstract: In the central nervous system, certain neurons store zinc within the synaptic vesicles of their axon terminals. This vesicular zinc can then be released in an activity-dependent fashion as an intercellular signal. The functions of vesicular zinc are not entirely understood, but evidence suggests that it is important for some forms of experiencedependent plasticity in the brain. The ability of neurons to store and release vesicular zinc is dependent on expression of the vesicular zinc transporter, ZnT3. Here, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…ZnT3 knockout mice showed increased basal dendrite length of layer 2/3 pyramidal neurons of the barrel cortex, as compared to wild-type mice [71].…”
Section: Zinc Increases Neurogenesismentioning
confidence: 86%
“…ZnT3 knockout mice showed increased basal dendrite length of layer 2/3 pyramidal neurons of the barrel cortex, as compared to wild-type mice [71].…”
Section: Zinc Increases Neurogenesismentioning
confidence: 86%
“…Few studies claim the necessity of zinc for experience-dependent plasticity in brain. A study conducted by McAllister et al reported the beneficial effects of EE are independent of zinc in terms of increased basal dendritic length and spine density in neurons of barrel cortex, striatum and amygdala [ 163 ]. Amyloid beta (Aβ) oligomer, a synaptotoxic agent, induced the impairment of LTP through downregulation of miRNA-132 expression and increased histone deacetylase (HDAC3), while EE produced beneficial effects through suppressing the effects of Aβ oligomer in hippocampus of wild-type mice [ 164 ].…”
Section: Non-therapeutic Modulators Of Dendritic Spinesmentioning
confidence: 99%
“…Additionally, Al could potentially interfere with the transport and distribution of Zn, hindering its arrival to critical neurons or speci c brain regions. Most notably, Al might disrupt the metabolism and utilization of Zn, resulting in its de ciency or ine cient level in the nervous system (McAllister et al, 2020). Apart from the prior-mentioned studies on the correlation between Al and Zn concentrations, this research further highlights the role of Zn as a pivotal mediator in the relationship between Al exposure and cognitive function.…”
Section: Correlation Analysis Between Wb and Qrt-pcr Veri Cation Resu...mentioning
confidence: 76%